Understanding Translation Errors in Social Media @Wonderfullindonesia Instagram Captions - Dewa Ayu Dian Utari; Ni Made Verayanti Utami (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Social media has become a key tool in global tourism promotion, including for Indonesia through its official Instagram account, @wonderfulindonesia. This article analyzes various translation errors found in the English captions translated from the original Indonesian versions. Using a qualitative descriptive approach and translation error analysis model, the study examined 30 Instagram posts from January to June 2025. The findings reveal a range of errors, including grammatical, lexical, syntactic, pragmatic, as well as collocational and idiomatic mistakes. These errors not only affect the clarity of the message but also reduce emotional appeal, hinder cross-cultural communication, and undermine the professional image of the government-managed account. Furthermore, translation inaccuracies decrease audience engagement, create inconsistent branding, and weaken Indonesia’s digital diplomacy efforts. The study emphasizes the need for professional translators who understand both cultural context and promotional purpose, to ensure that the language used is not only linguistically correct but also persuasive and communicative. By improving translation quality, Indonesia’s digital tourism promotion can more effectively attract international audiences and build a positive global image.